2022
DOI: 10.1001/jamainternmed.2021.7429
|View full text |Cite
|
Sign up to set email alerts
|

The MedSafer Study—Electronic Decision Support for Deprescribing in Hospitalized Older Adults

Abstract: interventions may reduce polypharmacy and the use of potentially inappropriate medications (PIMs); however, few studies have been large enough to evaluate the impact that deprescribing may have on adverse drug events (ADEs).OBJECTIVE To evaluate the effect of an electronic deprescribing decision support tool on ADEs after hospital discharge among older adults with polypharmacy.DESIGN, SETTING, AND PARTICIPANTS This was a cluster randomized clinical trial of older (Ն65 years) hospitalized patients with an expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(148 citation statements)
references
References 45 publications
3
132
0
Order By: Relevance
“…The MedSafer [18] trial enrolled 5698 patients 65 years and older who were taking 5 or more medications and survived to hospital discharge. The median age of the cohort was 78 years (IQR 71-86) and 50.2% or participants were female.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The MedSafer [18] trial enrolled 5698 patients 65 years and older who were taking 5 or more medications and survived to hospital discharge. The median age of the cohort was 78 years (IQR 71-86) and 50.2% or participants were female.…”
Section: Resultsmentioning
confidence: 99%
“…[12] For this COVID-SAFER: Nirmatrelvir-ritonavir study, we analyzed data from the 5698 patient cluster randomized MedSafer trial, which ran from August 2017 to January 2020. [14] Briefly, inclusion criteria identified patients 65-years and older, taking five or more medications, admitted to one of the 11 study hospitals. Data pertaining to medications and comorbidities were analyzed with the MedSafer deprescribing software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent randomized controlled trial using MedSafer in hospitalized patients demonstrated an increase in the amount of PIMs deprescribed compared with usual care alone, with a neutral impact on short-term ADEs in the 30-day post-hospital discharge. 23 Although polypharmacy and ADEs are well documented in patients on dialysis, few studies have reported on deprescribing interventions and follow-up outcomes for this population. Thus, the aims of this study were to (1) characterize the prescription patterns in a cohort of hospitalized patients with polypharmacy receiving maintenance intermittent dialysis, (2) identify PIMs that were flagged by MedSafer and subsequently deprescribed, and (3) describe the clinical outcomes following deprescribing in this subgroup of the largest inpatient deprescribing trial published to date.…”
Section: Introductionmentioning
confidence: 99%